Y = 2x – 5
Y = 2x – 3
Y = -3x+2
Y = -2x + 3
Y = 3/2x +1
Y = 3/2x – 1
Y = 2/3x + 3
Y = -2/3x + 1
Y = 5x – 2
Y = 2 – 5x
Y = -2x + 3
Y = -2/5x
M = -2/3 ; b = 2
M = -3/2 ; b = 2
M = 2/3 ; b = 2
M = 2/3 ; b = 3
Y = 5/2x + 6
Y = 5/2x - 6
Y = -2x + 6
Y = 2x – 6
113
157
137
123
4/3
3/4
-4/3
-3/4
Y = 3/4x + 4
Y = 4/3x - 4
Y = 4/3x + 4
Y = -4/3x + 4
X = -1
X = 2
X = -2
X = 1
X = 20
X = 4
X = 8
X = 16.6
Y = 3/2x + 2
Y = 2/3x - 2
Y = -2/3x -2
Y = -2/3x + 2
15 days
5 days
9 days
12 days
12
120
6
60
18
16
32
20
81
86
44
36
57
63
84
48
45
54
25
30
10
4
100
5
A
B
C
D
6
10
1250
20
Y-axis
Quadrant 2
Quadrant 1
Quadrant 3
4.5 = (r + c)12
4.5 = (r - c)12
12 = (r + c)4.5
12 = (r - c)4.5
2 km/h
4 km/h
6 km/h
8 km/h
20
2
28
-28
55
90
60
70
1.2 x 10^8 gallons
1.2 x 10^9 gallons
8.8 x 10^8 gallons
8.8 x 10^9 gallons
0
12
8
4
3.62 x 10^4
3.62 x 10^6
3.62 x 10^-4
3.62 x 10^-6
3.1 x 10^6
3.1 x 1^-6
3.1 x 10^7
3.1 x 10^-7
A
B
C
D
A
B
C
D
-64
-2
2
64
10
8
12
9
4x + 8
9x + 12
4x + 12
9x + 6
8x + 9c
8x + 10c
7x + 8c
7x + 7c + 2
12
9
8
16
3n + 3n + 3n = 33
(n + 2) + (n + 4) = 33
3n + (3n +2) + (3n + 4) = 33
3n + (n +2) + (n + 4) = 33
2w + 2(w + 6) = 362
W(w – 6) = 362
W(w + 6) = 362
6w – 6 = 362
C = p + 6
C = p
C = 6p + 6
C = 6p
10(y - x)
10y - x
10(x - y)
10x - 10y
22 = x + 221
22 = x - 221
221 = x + 22
221 = 22x
G + b = 28 and b = 2g + 2
G + b = 28 and b = 2g - 2
G + b = 28 and g = 2b + 2
G + b = 28 and g = 2b - 2
16x - 16
X
16x
16x + 16